Reduced Leukoaraiosis, Noncardiac Embolic Stroke Etiology, and Shorter Thrombus Length Indicate Good Leptomeningeal Collateral Flow in Embolic Large-Vessel Occlusion - Hashimoto, T.; Kunieda, T.; Honda, T.; Scalzo, F.; Ali, L.; Hinman, J.D.; Rao, N.M.; Nour, M.; Bahr-Hosseini, M.; Saver, J.L.; Raychev, R.; Liebeskind, D. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Acute leptomeningeal collateral flow is vital for maintaining perfusion to penumbral tissue in acute ischemic stroke caused by large-vessel occlusion. In this study, we aimed to investigate the clinically available indicators of leptomeningeal collateral variability in embolic large-vessel occlusion.MATERIALS AND METHODS: Among prospectively registered consecutive patients with acute embolic anterior circulation large-vessel occlusion treated with thrombectomy, we analyzed 108 patients admitted from January 2015 to December 2019 who underwent evaluation of leptomeningeal collateral status on pretreatment CTA. Clinical characteristics, extent of leukoaraiosis on MR imaging, embolic stroke subtype, time of imaging, occlusive thrombus characteristics, presenting stroke severity, and clinical outcome were collected. The clinical indicators of good collateral status (>50% collateral filling of the occluded territory) were analyzed using multivariate logistic regression analysis.RESULTS: Good collateral status was present in 67 patients (62%) and associated with independent functional outcomes at 3 months. Reduced leukoaraiosis (total Fazekas score, 0–2) was positively related to good collateral status (OR, 9.57; 95% CI, 2.49–47.75), while the cardioembolic stroke mechanism was inversely related to good collateral status (OR, 0.17; 95% CI, 0.02–0.87). In 82 patients with cardioembolic stroke, shorter thrombus length (OR, 0.91 per millimeter increase; 95% CI, 0.82–0.99) and reduced leukoaraiosis (OR, 5.79; 95% CI, 1.40–29.61) were independently related to good collateral status.CONCLUSIONS: Among patients with embolic large-vessel occlusion, reduced leukoaraiosis, noncardiac embolism mechanisms including embolisms of arterial or undetermined origin, and shorter thrombus length in cardioembolism are indicators of good collateral flow.LCSleptomeningeal collateral statusLVOlarge-vessel occlusion